High Performance Human Resource Development to Enhance National Competitiveness - Maetsong, Suwimon Maetsong; Pholpuntin, Sirote; Chaleysub, Sukum; Tungdamnernsawad, Supaporn (Mahachula Academic Journal, 2025)
This academic article aims to present concepts, theories, and applications of high-performance human resource development in strengthening national competitiveness. High-performance human resource development is a crucial mechanism for driving potential in an era of rapid technological and innovative changes, particularly as Thailand undergoes a significant transition from a labor-intensive economy to a knowledge-driven, technology-based, and innovation-oriented economy. High-performance human resource development must be built upon six strategic capabilities: human capital, learning, collaboration, strategic alignment, culture, and leadership. It should be driven through three key strategies: education, training, and personnel placement to achieve efficient and sustainable development. The article presents approaches for producing high-performance workforce in three main groups: workforce for current position replacement, job creators, and innovators. Key driving mechanisms include skill mapping, experiential learning promotion, and flexible education management. Furthermore, critical success factors include HR flexibility, technical and strategic HRM, and strategic workforce emphasis. High-performance human resource development requires systematic implementation to build a capable workforce that can drive national competitiveness.